Distance Accompanying Course in the Ukrainian Language Phonetics for Foreign Students at the Main Stage of Training. - Мирошниченко, Ю. М. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article analyzes the possibility of using distance learning/teaching language as a foreign one in general and the Ukrainian language phonetics in particular. The author focuses on the peculiarities of distance education in comparison with a traditional process of learning/teaching. It has been proposed to create a distance learning/teaching course in the Ukrainian language phonetics which will connect the principles of accompanying and correction phonetic courses for further use at the main stage of training.